Factors Responsible for Refusal of Insulin Administration in Diabetic Patients - Hussain, Syed Fayaz; Ali Shah, Syed Nasir; Ali Bukhari, Syed Muhammad Sajid Ali Bukhari; Naseem, Muhammad Rashid (Indus Journal of Bioscience Research, 2025)
Background: Despite being a core aspect of the management of diabetes, insulin therapy still continues to be refused or delayed by patients via certain perceived fears and beliefs. It is essential to understand these attitudinal barriers to facilitate improved compliance to the therapy and health status. Objective: To determine the frequency of factors leading to refusal of insulin administration in patients with diabetes. Study Design: Descriptive cross-sectional study. Duration and Place of Study: The study was conducted from April 2024 to September 2024 at the Department of Medicine, Shaikh Khalifa Bin Zayed Al Nahyan Hospital, CMH Rawalakot. Methodology: 127 diabetic patients aged between 18 and 60 years, counselled for insulin therapy but refused it or deferred it for a period of at least three months, were covered. The respondents were interviewed through a structured questionnaire, comprising demographic details, as well as various psychological, social, and practical factors associated with insulin refusal. Results: The mean age of participants was 41.30 ± 7.77 years, and the average BMI was 26.35 ± 2.90 kg/m². Most patients were male (66.9%), rural residents (54.3%), and had Type 2 diabetes (70.1%). The most commonly reported reason for insulin refusal was fear of social stigma (63%), followed by fear of pain (55.1%), cost concerns (51.2%), and interference with work and diet (50.4%). Additional notable factors included fear of hypoglycemia and dependency (both 49.6%), perceived disease progression (46.5%), feelings of self-blame (42.5%), and concerns about weight gain (40.9%). Conclusion: Our study has concluded that insulin refusal is influenced by a multifaceted interplay of social, psychological, and economic factors.